Experimental study on the vertical interface of thin-tile masonry. (20th November 2020) - Llorens, Joan; Llorens, Miquel; Chamorro, Miquel Angel; Gómez, Javier; Barris, Cristina
Highlights: The behaviour of mortar-tile vertical interface was analysed using the DIC technique. The multi-leaf wall masonry compressive strength equation was suitable for a two-leaf thin tile. Failure mode of thin-tile masonry is characterized by cracking at the mortar-tile vertical interface. Uniaxial compressive strength in the detachment is relevant for thin-tile masonry. In thin-tile masonry, the load is mainly carried by the thin-tile leaves. Abstract: This article presents the results of an experimental study on the structural behaviour of the vertical mortar thin-tile interface in thin-tile masonry. Four compression tests involving two- and three-leaf prisms made of two different types of mortar were carried out. The Digital Image Correlation (DIC) technique was used to capture the full-field displacement of the mortar thin-tile interface. The experimental results revealed that, while all the leaves presented a similar deformation in the longitudinal direction, transversally, the deformations tended to separate the mortar and tile leaf. Thus, it could be concluded that the failure mode of the thin-tile masonry was due to tensile stress perpendicular to the vertical thin-tile mortar interface (mode I), which seemed to be associated with the transverse deformation of the horizontal mortar joints. An analytical approach for the compressive strength of thin-tile masonry based on the usual equation available in the literature for unreinforced multi-leaf masonry walls has been presented. This model seems suitable for determining the compressive strength of thin-tile masonry, but has a more relevant role for mortar leaf.